LEGAL UNCERTAINTY AND CREDITOR PROTECTION IN THE BANKRUPTCY REGIME FOR INSURANCE COMPANIES IN INDONESIA (Lex localis - Journal of Local Self-Government, 2025)
This article examines the legal uncertainty surrounding Indonesia’s framework for insurance company insolvency, with a particular focus on creditor protection. While current regulations grant the Financial Services Authority (OJK) exclusive authority to initiate bankruptcy petitions to safeguard financial stability and the public interest, this centralized model raises significant concerns regarding transparency, procedural fairness, and the limited remedies available to policyholders and other creditors. Employing normative and doctrinal legal research methods, the study analyzes statutory provisions, judicial decisions, and theoretical perspectives on legal protection, certainty, and the economic role of law. A comparative analysis with the Netherlands, the United States, and Singapore reveals that these jurisdictions have developed more structured insolvency regimes and effective policyholder guarantee mechanisms. The findings demonstrate that Indonesia’s system, though normatively grounded, perpetuates legal uncertainty through excessive reliance on regulatory discretion, the absence of operational policyholder protection schemes, and delays in creditor remedies. To address these deficiencies, the study recommends objective criteria for OJK’s filing authority, acceleration of the Policy Guarantee Program under the Indonesia Deposit Insurance Corporation (LPS), enhanced judicial oversight, inter-agency coordination, and strengthened legal literacy for policyholders.